Diseño de una cartilla para la enseñanza de competencias básicas en contabilidad a mujeres del sector rural (2021)
Accounting is a discipline that, by identifying, recording and summarizing economic information, allows decision-making, therefore, it will be very useful for women in rural areas who market products or have businesses. For this reason, the objective of this project was to design a primer that would facilitate the learning of basic accounting skills for women in the rural sector.